IMPLEMENTASI KURIKULUM 2013 DALAM PEMBELAJARAN MENULIS TEKS BIOGRAFI (STUDI KASUS DI SMP NEGERI 4 KARANGANYAR) - Andriyana, Rizki Novita; Suwandi, Sarwiji; Saddhono, Kundharu (Universitas Sebelas Maret, 2019)
This study aims to describe the planning, implementation, implementation of learning, obstacles encountered, and efforts made to overcome obstacles in accordance with the Curriculum 2013, especially on learning to write biographical text in SMP Negeri 4 Karanganyar. The description of such planning, implementation, constraints and efforts to find out their compliance with the Curriculum 2013. This research is a descriptive qualitative research using case study approach with single strategy terpancang. The results of this study are: (1) Learning planning in the form of RPP in accordance with the Curriculum 2013, but there is discrepancy in the three RPP that is the time allocation in the core activities is not written in detail at each activity steps. (2) Implementation of biography text writing lesson in accordance with RPP but there is non-conformity to time allocation. Assessment done by teacher when the process of learning and writing practice. (3) Constraints faced by teachers: inadequate learning resources, lack of interest and poor readiness of students in biographical texts, and students have not fully adapted to the 2013 curriculum. Teachers 'efforts: seek additional references from other sources, enthusiastic students' enthusiasm with games , giving the lecture method to the students. Constraints faced by students: the difficulty of defining themes and structures in biographical texts. Efforts by students: searching from other sources and asking the teacher.